The Influence of CSR and Profitability On Value Companies with GCG As A Moderating Variable - Afifah, Dea Agnes; Mutmainah, Isbandriyati; Wahidhani, Eha Hasni (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of this research is to analyze the influence of CSR (Corporate Social Responsibility) and profitability on firm value with GCG (Good Corporate Governance) as a moderating variable in the Food and Beverages sub-sector companies listed on the Indonesia Stock Exchange (BEI) in the year 2022. The population in this study consists of Food and Beverages sub-sector companies listed on the Indonesia Stock Exchange during the 2022 period. The sample size for this study is 30 companies. The sampling method employed is purposive sampling, and hypothesis testing is conducted using Moderated Regression Analysis. The results of this research indicate that CSR has a significant impact on firm value, profitability has a significant impact on firm value, and GCG can moderate the influence of CSR and profitability on firm value. Keywords: CSR, Profitability, Firm Value, GCG